2014
DOI: 10.1186/s40560-014-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma is ineffective in correcting mildly elevated PT-INR in critically ill children: a retrospective observational study

Abstract: BackgroundFresh frozen plasma transfusion is widely utilized in pediatric clinical practice to correct mild coagulopathy. Several studies on adult population have shown that transfusion of plasma cannot effectively correct mild coagulopathy when international normalized ratio (INR) is ≤1.5. Much controversy exists about the generalization of this finding for pediatric populations, especially since pediatric dosages often exceed those in adults. The aim of this study is to determine the prevalence of plasma tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…It has been shown that there was not an association of transfusion with correction of PT/INR or improved survival (38) . Furthermore, studies in both adults and children showed that plasma transfusions to correction for mildly higher PT/INR routinely fail to normalize this value and expose patients to unnecessary risk and delays (39)(40)(41) . The major bleeding rates were similar between the groups in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there was not an association of transfusion with correction of PT/INR or improved survival (38) . Furthermore, studies in both adults and children showed that plasma transfusions to correction for mildly higher PT/INR routinely fail to normalize this value and expose patients to unnecessary risk and delays (39)(40)(41) . The major bleeding rates were similar between the groups in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for infectious transmission associated with transfusion, it is the risk of allergic reaction, acute hemolytic reactions, febrile nonhemolytic transfusion reactions, transfusion related circulatory overload, and transfusion related acute lung injury that are equally life-threatening and far more common. 13,14,24,31 It has been reported that percentages of inappropriate FFP transfusions range from 10 to 83 per cent, 13,31 with the most frequent indication being correction of a prolonged INR in the absence of bleeding. 13,14,16,31 However, published reports on FFP transfusion have reported minimal to no effect when transfusion was used for prophylaxis or as therapeutic agent for bleeding 13 A systematic review of 80 randomized controlled trials investigating the clinical use of FFP concluded no consistent evidence of benefit for prophylactic and therapeutic use across a range of indications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,24,31 It has been reported that percentages of inappropriate FFP transfusions range from 10 to 83 per cent, 13,31 with the most frequent indication being correction of a prolonged INR in the absence of bleeding. 13,14,16,31 However, published reports on FFP transfusion have reported minimal to no effect when transfusion was used for prophylaxis or as therapeutic agent for bleeding 13 A systematic review of 80 randomized controlled trials investigating the clinical use of FFP concluded no consistent evidence of benefit for prophylactic and therapeutic use across a range of indications. 33 Although the most common abnormality noted in our study was an elevated PT value (38.9%), it is the INR values that customarily direct treatment with FFP before procedures.…”
Section: Discussionmentioning
confidence: 99%
“…As transfusões de PFC na instituição são frequentemente mal indicadas e ainda assim prescritas em doses muitas vezes insuficientes, reforçando mais um caráter de conforto psicológico para os médicos que uma necessidade estabelecida, dada a baixa capacidade de correção de coagulopatias estabelecidas, mesmo em doses adequadas (SOUNDAR et al, 2014).…”
Section: Discussionunclassified